Challenges and strategies in building a foundational digital health data integration ecosystem: a systematic review and thematic synthesis - Ambalavanan, Radha; Snead, R Sterling; Marczika, Julia; Towett, Gideon; Malioukis, Alex; Mbogori-Kairichi, Mercy (Frontiers in Health Services, 2025)
BackgroundChronic conditions require robust healthcare data integration to support personalized care, real-time decision-making, and secure information exchange. However, fragmented data ecosystems disrupt interoperability, complicate patient-centered care (PCC), and present challenges for incorporating genomic data into clinical workflows.ObjectiveThis systematic review with thematic synthesis aims to identify key challenges and synthesize existing strategies from the literature to inform the development of a foundational digital health data integration ecosystem.MethodsFollowing PRISMA guidelines, we systematically screened literature across multiple databases. A thematic synthesis approach was used to categorize findings into three primary themes: interoperability, PCC, and genomic data integration.ResultsA total of 161 studies were included. Key challenges identified include semantic misalignment across commonly used healthcare standards such as HL7 FHIR and SNOMED CT, limited cross-system data exchange, inadequate patient engagement features in EHRs, and concerns regarding the security and clinical utility of genomic data. Strategies described across the literature include ontology-based interoperability models, AI-supported PCC frameworks, and blockchain-enabled genomic data governance.ConclusionBy analyzing current methodologies, research gaps, and implementation challenges, this review offers an evidence-based foundation to guide future advancements in healthcare data integration. It supports the development of scalable, privacy-preserving, and ethically governed data-sharing infrastructures that enable personalized medicine and real-time clinical interventions.Systematic Review Registrationhttps://osf.io/c2xvw.